Implementasi Storytelling Marketing Sutasoma Hotel By The Tribrata dalam Membangun Brand Awareness - Najwa Allysa Ansyari (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research explores the implementation of storytelling marketing by Sutasoma Hotel by The Tribrata in its effort to build brand awareness. Given the intense competition in the hospitality industry, marketing strategies that employ emotional approaches through storytelling have become essential to differentiate brands in the minds of consumers. This study uses a qualitative approach with a case study method. The primary theoretical framework is Walter Fisher’s Narrative Paradigm, which emphasizes that humans make sense of the world through stories. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic analysis techniques. The findings reveal that Sutasoma Hotel’s storytelling marketing highlights cultural values, guest experiences, and luxury visualization to build emotional engagement with its audience. This strategy has proven effective in increasing brand awareness, strengthening brand identity, and creating memorable customer experiences. The study also finds that the use of social media plays a crucial role in disseminating narratives and expanding audience reach. Therefore, storytelling marketing is a relevant and impactful communication strategy for building brand awareness in the hospitality sector.